2001
DOI: 10.1136/pmj.77.907.329
|View full text |Cite
|
Sign up to set email alerts
|

Acute diquat poisoning with intracerebral bleeding

Abstract: A case of severe diquat poisoning complicated by the development of aggressive behaviour, oliguric renal failure, and intracerebral bleeding is described. The patient was successfully managed and made a complete recovery. In this paper special attention has been given to the major clinical diVerences between diquat and paraquat intoxication. (Postgrad Med J 2001;77:329-332)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…The herbicide diquat, which is structurally similar to paraquat, has replaced paraquat where its use has been prohibited due to a suggested association with Parkinson’s disease (McCormack et al 2002 ) and is now in widespread use as an agricultural and home use herbicide. Diquat is known to be toxic acutely in high doses (Hantson et al 2000 ; Jones and Vale 2000 ; Jovic-Stosic et al 2009 ; Saeed et al 2001 ; Schmidt et al 1999 ) and evidence of Parkinsonism after use of diquat has been suggested (Sechi et al 1992 ). Acutely, diquat causes intracerebral haemorrhage particularly in the white matter but also in the brainstem with a necrotic appearance (Vanholder et al 1981 ).…”
Section: Introductionmentioning
confidence: 99%
“…The herbicide diquat, which is structurally similar to paraquat, has replaced paraquat where its use has been prohibited due to a suggested association with Parkinson’s disease (McCormack et al 2002 ) and is now in widespread use as an agricultural and home use herbicide. Diquat is known to be toxic acutely in high doses (Hantson et al 2000 ; Jones and Vale 2000 ; Jovic-Stosic et al 2009 ; Saeed et al 2001 ; Schmidt et al 1999 ) and evidence of Parkinsonism after use of diquat has been suggested (Sechi et al 1992 ). Acutely, diquat causes intracerebral haemorrhage particularly in the white matter but also in the brainstem with a necrotic appearance (Vanholder et al 1981 ).…”
Section: Introductionmentioning
confidence: 99%
“…These anions may react to form hydrogen peroxide and subsequently the highly reactive hydroxyl radical, which may then cause lipid peroxidation and cell death [ 159 , 160 ]. Another factor contributing to toxicity is the depletion of nicotinamide adenine dinucleotide phosphate with a bound hydrogen ion (NADPH), as both herbicide redox cycling and hydrogen peroxide detoxification via glutathione are NADPH dependent [ 159 , 161 ]. In addition to redox-cycling, there is some evidence that paraquat may be able to interact with enzymatic targets in the CNS, such as AChE and butylcholinesterase [ 162 ].…”
Section: Introductionmentioning
confidence: 99%
“…In severe and usually fatal cases of diquat poisoning, coma has also been reported [ 160 ]. Severe neurological and neuropsychiatric complications due to brain stem infarction and/or intracranial haemorrhage have also been described [ 161 , 163 , 166 ].…”
Section: Introductionmentioning
confidence: 99%
“…Saeed S A M . (2001) also reported an intracerebral bleeding following acute paraquat ingestion (19). The report was based on a 52 year-old male who had ingested about 160 ml of "Weed killer".…”
mentioning
confidence: 99%